Optimising Exome Prenatal Sequencing Services (EXPRESS): a study protocol to evaluate rapid prenatal exome sequencing in the NHS Genomic Medicine Service [version 2; peer review: 2 approved] - Melissa Hill; Sian Ellard; Naomi Fulop; Jane Fisher; Mark Kroese; Marian Knight; Kerry Leeson-Beevers; Jean Ledger; Dominic McMullan; Alec McEwan; Stephen Morris; Rhiannon Mellis; et al. (NIHR Open Research, 2022)
Background: Prenatal exome sequencing (ES) for the diagnosis of fetal anomalies was implemented nationally in England in October 2020 by the NHS Genomic Medicine Service (GMS). The GMS is based around seven regional Genomic Laboratory Hubs (GLHs). Prenatal ES has the potential to significantly improve NHS prenatal diagnostic services by increasing genetic diagnoses and informing prenatal decision-making. Prenatal ES has not previously been offered routinely in a national healthcare system and there are gaps in knowledge and guidance. Methods: Our mixed-methods evaluation commenced in October 2020, aligning with the start date of the NHS prenatal ES service. Study design draws on a framework developed in previous studies of major system innovation. There are five interrelated workstreams. Workstream-1 will use interviews and surveys with professionals, non-participant observations and documentary analysis to produce in-depth case studies across all GLHs. Data collection at multiple time points will track changes over time. In Workstream-2 qualitative interviews with parents offered prenatal ES will explore experiences and establish information and support needs. Workstream-3 will analyse data from all prenatal ES tests for nine-months to establish service outcomes (e.g. diagnostic yield, referral rates, referral sources). Comparisons between GLHs will identify factors (individual or service-related) associated with any variation in outcomes. Workstream-4 will identify and analyse practical ethical problems. Requirements for an effective ethics framework for an optimal and equitable service will be determined. Workstream-5 will assess costs and cost-effectiveness of prenatal ES versus standard tests and evaluate costs of implementing an optimal prenatal ES care pathway. Integration of findings will determine key features of an optimal care pathway from a service delivery, parent and professional perspective. Discussion: The proposed formative and summative evaluation will inform the evolving prenatal ES service to ensure equity of access, high standards of care and benefits for parents across England.